(untitled) (Boston, 2005)
Quality Management's all-new section provides the framework for designing effective administrative systems for quality management. New coverage of Six Sigma combines with a wealth of new examples from industry to communicate both the theory and reality of quality management today.
Keywords: Quality control,Quản trị chất lượng